Puisi Sufistik Jalaludin Rumi Tentang Makna Kematian (Analisis Psikoanalisis Jacques Lacan Pada Makna Kematian) - A Zahid (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2019)
The Sufistic poem Jalaludin Rumi signals the living creature that death is a real entity. However, death is illustrated as a pleasant experience for believers, a last resort to the creator. Death is not frightening, but